Chapter 1 Introduction - Franklin, Sophie (Taylor & Francis, 2024)
The introduction to this collection sets out the stakes of research on consent in this contemporary moment. It explores current debates about the limitations of consent as a framework for sexual ethics and argues for retaining consent as both a legal standard and a way of opening up questions of autonomy, care, and agreement across varied social contexts. It puts forward a view of the value of multidisciplinary and intersectional approaches to consent that take into account the nuances of precise contexts and individual identities. Offering an overview of consent studies in contemporary scholarship, a contextualisation of this volume and its approach, and a summary of the individual chapters included, the Introduction sets out why consent and its legacies, representations, and future potential continue to matter in our present moment.